Pengolahan Daun Singkong Menjadi Dendeng Sebagai Alternatif Pengganti Daging Sapi - Nur Al-Faida; Fitriani Abdal; Sukriadi Sukriadi; Irawati Irawati; Mia Mariana Mote; Yaningsi Novita; Amos Edowai (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Processing cassava leaves into beef jerky can produce jerky with a crunchier texture and a taste similar to beef jerky. Making cassava jerky through the substitution of tapioca flour is carried out to improve quality so that jerky can be obtained as a source of protein. Apart from protein, cassava leaf jerky also contains dietary fiber so it can be used as a functional food. This service activity was carried out with the aim of optimizing the use of cassava leaves to make delicious, nutritious processed products and as a substitute for beef, which is more expensive than cassava leaves but has almost the same nutritional value. Processing cassava leaves into beef jerky is carried out in several stages of the process by adding other ingredients and spices to produce jerky with a delicious taste. Apart from being used for family consumption, this cassava leaf jerky can also be marketed so that it can increase the family's economy in the local area. This activity was carried out at the posyandu in one of the residents' houses located on Jalan Padat Karya Kalibobo, Nabire Regency. The implementation stage of this activity starts from preparation, implementation and evaluation. This service activity was successful, seen from the enthusiasm of the women during the process of processing cassava leaves into beef jerky.